Fatal intoxication related to two new arylcyclohexylamine derivatives (2F-DCK and 3-MeO-PCE). (July 2021) - Gicquel, Thomas; Richeval, Camille; Mesli, Vadim; Gish, Alexandr; Hakim, Florian; Pelletier, Romain; Cornez, Raphael; Balgairies, Axelle; Allorge, Delphine; Gaulier, Jean-michel
Abstract: Continuous development and rapid turnover of drug market of new psychoactive substances (NPS) make it difficult to obtain up-to-date analytical methods for efficient detection of intoxication cases with new substances: no analytical data and no previously published concentration values in biological samples are indeed available. In this context, we aim to report the first fatal case involving two newly emerging arylcyclohexylamine derivatives (a group of dissociative ketamine-based substances): 2-fluoro-deschloroketamine (2F-DCK) and 3-methoxyeticyclidine (3-MeO-PCE). A 42-year-old man was found dead at his home with three plastic bags of "research chemicals" powders near him. Comprehensive screenings of drugs and toxic compounds as well as more selective assays (performed using NMR, HS-GC-FID, LC-MS/MS and LC-HRMS methods) allowed (1) to identify the three unknown powders, 2F-DCK, 3-MeO-PCE, and 5-methoxy- N, N -dimethyltryptamine (5-MeO-DMT, a hallucinogenic tryptamine-related NPS), with purity above 95%, and (2) to determine peripheral blood (1780, 90, and 52 µg/L), urine (6.1, 6.3, and 2.2 mg/L), bile (12, 3.5, and 1.7 mg/L), and vitreous humour (1500, 66 and 155 µg/L) concentrations of 2F-DCK, 3-MeO-PCE and 5-MeO-DMT, respectively. In addition, toxicological results also revealed recent use of cannabis, cocaine, and amphetamine by the victim, and hair analysis draw pathway of addiction (including experiments with various other NPS) for several months before death. This fatality was considered as the consequence of respiratory depression in a poly-drug user due to a "cocktail effect" of concurrent intakes of 2F-DCK (mainly), 3-MeO-PCE, 5-MeO-DMT, amphetamine, and cocaine. In addition, this case report provides analytical data that could support subsequent toxicological result interpretation in forensic cases involving such arylcyclohexylamine derivatives.